Eggs viability of Aedes aegypti Linnaeus (Diptera, Culicidae) under different environmental and storage conditions in Manaus, Amazonas, Brazil - V. C. Soares-Pinheiro; W. Dasso-Pinheiro; J. M. Trindade-Bezerra; W. P. Tadei (Brazilian Journal of Biology)
Abstract The viability of Aedes aegypti eggs was assessed in the Amazon region. The eggs were maintained under different conditions: indoors (insectarium) and outdoors (natural environment), as well as in different storage types (plastic cup, paper envelope, plastic bag) for different days. Egg viability was measured as the mean of hatchings observed from egg-bearing sheets of filter paper immersed in water, using three sheets randomly selected from each storage type and at both sites. There were significant differences in the viability of Ae. aegypti eggs with respect to the location (F=30.40; DF=1; P<0.0001), storage type (F=17.66; DF=2; P<0.0001), and time of storage (F=49.56; DF=9; P<0.0001). The interaction between storage site versus storage type was also significant (F=15.96; DF=2; P<0.0001). A higher hatching mean was observed for the eggs kept in the insectarium than for those outdoors (32.38 versus 7.46). Hatching rates of egg batches stored for 12 to 61 days ranged between 84 and 90%. A reduction was observed between 89 and 118 days, with values of 63 and 48%, respectively. With respect to type of storage, mean egg hatching was higher for the eggs in plastic cups (44.46). It was concluded that the viability of the eggs of Ae. aegypti in the Amazon region remains high up to 4 months, after which it declines drastically, although in this study hatching occurred for up to 8 months in very low percentages.